Indonesia-Germany cooperation in efforts to improve vocational education levels: Analysis of the Ausbildung program - Rafflialdi Hugo Atthareq; RMT Nurhasan Affandi (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2023)
The quality of Indonesian human resources still needs improvement to compete in the international world. Currently, the international market requires a lot of competence in technical skills in the vocational field. For this reason, Indonesia focuses on developing vocational training and education. This demand was not fulfilled because Indonesian vocational graduates did not have the right skills. With abundant but ineffective resources, Indonesia must learn much from other countries, including Germany. The output of this international collaboration is the Ausbildung program or Apprenticeship Training. This article seeks to reveal how Indonesian-Germany cooperation in vocational education impacts the two countries by using a qualitative method of reviewing documents and interviews with relevant sources. Findings from this article's cooperation opens up new opportunities for exploiting intellectual labor, which is neo-capitalism. In terms of salary, the wages received by Indonesian workers are far below the minimum wage that should be given to professional workers in Germany.